Squeeze Flow of Ethylene Glycol-based Carbon Nanotube with the Influence of Joule Heating, Viscous Dissipation and Chemical Reactions (European Journal of Pure and Applied Mathematics, 2025)
In this article, we discuss a hydrothermal model that describes the flow of Carbon Nanotube (CNT) nanofluid between squeezing plates while accounting for joule heating, viscous dissipation and homogeneous-heterogeneous chemical reactions. The $(Alumina)$ and CNTs (single-wall carbon nano tube [SWCNTs] or multi-wall carbon nano tube [MWCNTs]) have been used as nanoparticles with a base fluid Ethylene glycol with water ($Alumina+C_2H_6O_2-H_2O$). The homotopy analysis technique (HAM) included into Mathematica and the MATLAB worked in BVP4c are used to approve and verify the results. We obtain that the current results have the best agreement with the previous literature for specific precisely specified occurrences. The residual errors of the HAM method have been shown physically and numerically for SWCNT and MWCNT. The other embedding parameters like Reynolds squeeze parameter, Prandtl number, volume fraction, schmit number and Eckert number have been intended and discussed.  The aim of this research is the improvement towards the consumption of energy in the field of engineering and industry. Furthermore, from the results it has been noted that the based on the data the MWCNTs have a stronger effect on velocity, temperature distribution, homogeneous and heterogeneous chemical reactions profiles, which is shown by graphs and tables.
Keywords: nanofluid; homotopy analysis; viscous dissipation